Study on the relationship between sedentary screen time and dyslipidemia in freshmen of a university in Hubei province - WU Juan; WANG Yan; ZHANG Jin; HE Minghui; HE Wanhong; LUO Yushuang; GU Yihan; ZHENG Chenyang; LIU Yanli; WANG Jing (Yixue xinzhi zazhi)
Objective To explore the relationship between screen-based sedentary time and dyslipidemia among college students, and to provide a basis for the prevention and control of dyslipidemia in adolescents.Methods Newly enrolled college students from a university in Hubei province in September 2021 were selected for the study, and a questionnaire survey and physical examination were conducted from September to October of the same year. The average daily screen sitting time of the respondents in the past year was collected through questionnaires. The height, weight, blood pressure and other indexes were obtained through physical examination, and the biochemical indexes of blood lipids (triglyceride, total cholesterol, low-density lipoprotein, high-density lipoprotein) and blood glucose were detected. Binary Logistic regression, restricted cubic spline and subgroup analysis were used to analyze the association between sedentary time and dyslipidemia.Results A total of 3,383 college students were included, with an average screen-based sedentary time of (4.44±2.29) h/d. There were 598 cases of dyslipidemia among college students, and the overall prevalence of dyslipidemia was 17.68%. The prevalence of elevated cholesterol, elevated triglycerides, elevated low-density lipoprotein, and decreased high-density lipoprotein were 4.76%, 3.72%, 4.29%, and 7.06%, respectively. The mean screen-based sedentary time in the dyslipidemia population was (4.60±2.21) h/d, which was longer than the mean screen-based sedentary time in the normolipidemic population (4.41±2.30) h/d, but the difference was not statistically significant (P=0.062). Binary Logistic regression analysis showed that dyslipidemia in college students was positively correlated with screen-based sedentary time after correcting for relevant factors such as gender, age, BMI, and history of hypertension, with screen-based sedentary time